Development of interactive learning media in learning (PJOK) athletic material for short distance running 100 meters for class X students of SMA Negeri 2 Denpasar - Putu Merta Adi Kusuma Jaya; I Ketut Semarayasa; I Gede Suwiwa (Bravo's: Jurnal Program Studi Pendidikan Jasmani dan Kesehatan, 2025)
This Research and Development aims to develop interactive learning media in learning (PJOK) material for 100 meter short distance running athletics for class X students which is packaged in the form of a website. This research uses the Research and Development (R&D) method using the ADDIE development model which consists of 5 stages, namely, analysis, design, development, implementation and evaluation. Data collection in this study used a questionnaire on a score scale. Data analysis uses qualitative and quantitative descriptive analysis. Based on the research results, it shows that the learning content expert test obtained a result of 93.3% (very valid), the learning design expert test obtained 100% (very valid), the learning media expert test obtained 98.4% (very valid). Furthermore, product development through individual trials obtained 98.7% (very valid), small group trials obtained 98% (very valid), large group trials obtained 97.9% (very valid). The conclusions obtained from this research and development were stated to be very feasible and usable. Suggestions to educators to implement interactive learning media for 100 meter short distance running packaged in website form on relevant PJOK subjects.